THE EFFECT OF EMPLOYEE ENGAGEMENT AND WORK LIFE BALANCE ON KNOWLEDGE SHARING MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON LECTURERS OF PATTIMURA UNIVERSITY AMBON - Alfa P Siwalette; Conchita Valentina Latupapua; Gerrit Pentury (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study examines the impact of employee engagement (EE) and work-life balance (WLB) on knowledge sharing (KS), with organizational citizenship behavior (OCB) as a mediating variable among faculty members at Pattimura University. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), data were collected from 91 faculty members selected through proportionate stratified random sampling. The results reveal that EE has a significant positive effect on KS, indicating that highly engaged faculty members are more likely to share knowledge. However, WLB does not significantly influence KS, suggesting that work-life balance alone is insufficient to drive knowledge-sharing behaviors. Both EE and WLB significantly impact OCB, confirming that faculty members with high engagement and work-life balance tend to exhibit more discretionary behaviors. Additionally, OCB positively affects KS, yet it does not mediate the relationships between EE and KS or WLB and KS, implying that knowledge-sharing behaviors occur independently of discretionary organizational contributions. These findings emphasize the importance of institutional strategies that enhance faculty engagement, create collaborative platforms, and foster a culture of knowledge exchange. By implementing engagement-driven policies and structured knowledge-sharing mechanisms, academic institutions can optimize faculty performance and strengthen their knowledge ecosystems, ultimately enhancing educational quality and institutional innovation.